Effects of the Care Training Program on Application Skills of Caregivers of Older Adults Stroke Survivors in Communities and Clinical Outcomes - Wimolphan, Pawadee; Jiteurangkoon, Patcharee (Journal of The Royal Thai Army Nurses, 2022)
This quasi-experimental research aimed to test effects of the care training program on application skills of caregivers of older adults stroke survivors in communities and clinical outcomes. Samples were sixty caregivers of older adult stroke survivors living in Wiangchai district, Chiangrai.Those samples with purposive sampling were equally divided into an experimental and a control group. The experimental group received 8 weeks care training program, while the control group was not getting any treatment. Application skills and clinical outcomes were measured at 4-weeks after the intervention completion. Research instruments were 1) experimental tools: the care training program included the manual of cerebrovascular disease in older adults and the caring, lesson plan, and VDO. 2) collection tools: demographic data, measure tool for the ability of care, and procedural skills practice. All tools were tested for the validity from five experts; CVI = 1. Additionally, the assessment tool was tested for reliability; KR 20 =.812. Dependent t-test was for the mean difference testing of the application skills score, and number of complications after the experiment between two groups. Furthermore, Chi-square test was for the difference of numbers of samples with each level of pressure sores. Findings: Application skills of the experimental group were significantly higher than control group (p<.001). The Incidence of falls in experimental group was lower than the control group (p<.05). No significant difference of pressure sore between two groups (p <.213). Results of this study could be applied for daily care plan of older adults stroke survivors in communities.